Efektivitas Pelaksanaan Pelayanan Kearsipan Pada Dinas Pendidikan Kabupaten Serdang Bedagai - Andri Widiani; Mawaddah Irham (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine the effectiveness of the implementation of archival services at the Serdang Bedagai Regency Education Service. This research uses a qualitative descriptive method, namely research that describes the effectiveness of archival implementation at the Serdang Bedagai Regency Education Office. The results of this research show that the Serdang Bedagai Regency Education Office has implemented various policies and procedures in order to increase the effectiveness of archival services. There are clear arrangements regarding the management, storage and maintenance of important archives. Although there have been efforts to improve the effectiveness of archival services, there are several challenges that need to be overcome.